Characterising and mapping a potential new source of wheat stem rust resistance - Maqolo, Kholosa (University of the Free State, 2020)
Stem or black rust caused by Puccinia graminis f. sp. Pers. tritici Eriks. & E. Henn (Pgt) is an important disease of wheat (Triticum aestivum L.) as outbreaks of the disease contribute to increased input costs through the application of fungicides and often result in lower yield and quality of the crop. Upon appearance of Pgt race Ug99 in Uganda, known for its virulence against the once widely deployed stem rust resistance (Sr) gene Sr31, there has been an increased urgency among wheat scientists to identify and deploy new sources of resistance. The aim of this study was to characterise and map a potential new source of stem rust resistance in two durum derived wheat lines M3283_4 and M3192_7. Parental lines, M3283_4 and M3192_7 (resistant) and Line 37-07 (susceptible) were screened with molecular markers for the presence of 13 designated Sr-genes (Sr2, Sr13, Sr22, Sr25, Sr26, Sr31, Sr32, Sr36, Sr39, Sr42, Sr55, Sr57 and Sr58). Of these only Sr13, located on chromosome 6A, was detected in the two resistant parental lines. Crosses were made between Line 37-07 and the resistant lines (M3283_4 and M3192_7) to produce F2 mapping populations. To determine how rust resistance segregated in these populations, phenotypic evaluation was performed by inoculating the seedlings with urediniospores of Pgt race PTKST, the most virulent member of the Ug99 race group in South Africa. The phenotypic evaluation of the F2 populations and F3 families produced Mendelian segregation ratios evident of a single dominant Sr-gene. Consequently, an allelism test was performed by making a top cross between the two resistant parents. Phenotyping of the derived F2’s indicated that either the same Sr-gene or a closely linked gene is present in the two resistant parents. Genotyping was performed to detect polymorphic loci between the three parental lines. In total, 170 simple sequence repeat (SSR) markers were screened, of which 86 and 85 were polymorphic between M3283_4 and M3192_7, respectively. Bulk segregant analysis (BSA) was used to screen the polymorphic markers on the Line37-07/M3283_4 and Line37-07/M3192_7 F2 bulks, individuals within the bulks and the entire F2 populations to identify markers closely linked to stem rust resistance. Two markers, Sr13 and gwm427 (both located on chromosome 6A) were consistently found closely linked to the gene(s) conferring resistance. A partial linkage map was drawn depicting the position of the resistance gene(s) relative to the closely linked markers. Marker Sr13 explained 62% and 22% of the phenotypic variation for Pgt race PTKST in populations Line37-07/M3283_4 and Line37-07/M3192_7, respectively. Furthermore, marker gwm427 explained 76% and 39% of the phenotypic variation for Pgt race PTKST, in populations Line37-07/M3283_4 and Line37-07/M3192_7, respectively. The effectiveness of the two markers was successfully validated using F3 families. Semi-thermal asymmetric reverse polymerase chain reaction (STARP) marker analysis was also performed to detect which haplotype of Sr13 was present. The Sr13a haplotype was detected in both resistant parents. The combined results from phenotyping and genotyping suggest that Sr13 is present in both M3283_4 and M3192_7 as it is known to confer resistance to Pgt race PTKST. Furthermore, results from the SSR markers used to detect the Sr13 gene was supportive and the diagnostic STARP marker Rwgsnp37 confirmed the presence of Sr13. Future work should include fine mapping through screening molecular markers known to map in the distal region of chromosome 6A. The resistance gene could be combined with other known effective Sr-genes in an effort to prolong resistance.
Keywords: Dissertation (M.Sc. (Plant Sciences ( Plant Breeding))--University of the Free State, 2020; Bulk segregant analysis; Puccinia graminis f. sp. tritici; Resistance breeding; Semi-thermal asymmetric reverse PCR; Simple sequence repeats; Sr13; Triticum aestivum